Vegetative and productive aspects of organically grown coffee cultivars under shaded and unshaded systems - Ricci, Marta dos Santos Freire; Rouws, Janaina Ribeiro Costa; Oliveira, Nelson Geraldo de [UNESP]; Rodrigues, Marinete Bezerra (Universidade de São Paulo (USP), Escola Superior de Agricultura Luiz de Queiroz (ESALQ), 2011)
Although Coffea arabica species has its origin in the African understories, there is great resistance on the part of the Brazilian producers for growing this species under agroforestry systems as they fear that shading reduces production. This study aimed at evaluating some vegetative traits and the productivity of organically grown coffee (Coffea arabica L.) cultivars under shaded and unshaded systems. Twelve treatments consisting of two cultivation systems (shaded and unshaded) and six coffee cultivars were arranged in randomized blocks with four replicates, in a split-plot scheme. Shading was provided by banana (Musa sp.) and coral bean plants (Erythrinaverna). Shading delayed fruit maturation. Late maturation cultivars, such as the Icatu and the Obatã, matured early in both cultivation systems, while medium and early maturation cultivars presented late maturation. Cultivation in the shaded system increased the leaf area and the number of lower branches, decreased the number of productive nodes per branch, and increased the distance between the nodes and the number of leaves present in the branches. Cultivation in the unshaded system presented greater number of plants with branch blight in relation to plants grown in the shade. The productivity of the cultivars was not different, at 30.0 processed bags per hectare in the shaded system, and 25.8 processed bags per hectare in the unshaded system. The most productive cultivars in the shaded system were the Tupi, the Obatã, and the Catuaí, while no differences between cultivars were obtained in the unshaded system.
Keywords: Coffea arabica L; organic coffee; agroforestry system; productivity